2012
DOI: 10.1016/j.cct.2012.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Examination of a telephone-based exercise intervention for the prevention of postpartum depression: Design, methodology, and baseline data from The Healthy Mom study

Abstract: Research indicates that exercise is an efficacious intervention for depression among adults; however, little is known regarding its efficacy for preventing postpartum depression. The Healthy Mom study was a randomized controlled trial examining the efficacy of an exercise intervention for the prevention of postpartum depression. Specifically, postpartum women with a history of depression or a maternal family history of depression (n=130) were randomly assigned to a telephone-based exercise intervention or a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 54 publications
2
16
0
2
Order By: Relevance
“…This study found a negative relationship between anxiety and social support from the family, similar to the study by Lewis et al. (), but no relationship between anxiety and social support from the husband, as reflected in the study of Siu et al. ().…”
Section: Discussionsupporting
confidence: 89%
“…This study found a negative relationship between anxiety and social support from the family, similar to the study by Lewis et al. (), but no relationship between anxiety and social support from the husband, as reflected in the study of Siu et al. ().…”
Section: Discussionsupporting
confidence: 89%
“…The majority of the studies (n=8) were conducted in the USA [27,30,31,34,35,37,40,41], two in the UK [4,28] and two in China [7,39]. One study was conducted in each of the following countries: Canada [29], Mexico [33], Norway [8], Hungary [32], France [5], Iran [26], Australia [6], Denmark [36], South Africa [25], Brazil [38].…”
Section: Settingmentioning
confidence: 99%
“…Lewis et al [35] examined the relation between employment status and PPD among high-risk women. This was a post hoc analysis from a previously conducted RCT, which was also included in this review and is described in more detail below (see [34]). 124 healthy women (six participants were lost to follow-up), who had a (maternal family) history of depression aged between 18-42 years have been examined.…”
Section: Psychosocial Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these include difficulties in combining child care and face-to-face psychological interventions, not knowing where to go to receive treatment, time limitations, transportation difficulties, social stigma associated with mental illness, and fear that their baby could be removed from their care. [28][29][30][31][32] In the light of the previous findings, the goal of this study was to review how Information and Communication Technologies (ICTs) have been used in PeD screening and to discuss to which extent they might help overcome some of the barriers presented previously. During the past years, the use of ICTs in the health service industry (eHealth) has increased spectacularly, arguably because of the decrease in their cost and their increased availability in the general population.…”
Section: Introductionmentioning
confidence: 99%